Proteomic characterization of Shiitake (Lentinula edodes) post-harvest fruit bodies grown on hardwood logs and isolation of an antibacterial serine protease inhibitor. Issue 1 (January 2023) - Domingo, Guido; Chiodaroli, Luca; Parola, Simone; Marsoni, Milena; Bracale, Marcella; Vannini, Candida
Abstract: Lentinula edodes (Shiitake) is one of the most heavily cultivated mushrooms in the world with proven antioxidant and antibacterial properties, among others. Evidence indicates that the choice of mushroom cultivation technique strongly influences the production of bioactive compounds, but to date the nature of many of these compounds has not been fully established. This work focuses on the proteomic characterization of L. edodes to highlight the main active processes two days after harvest and elucidates the proteins involved in the known antioxidant and antibacterial proprieties of Shiitake fruit bodies cultivated on oak logs. A label-free approach allowed us to identify a total of 2702 proteins which were mainly involved in carbohydrate and protein metabolism, cell growth and replication, indicating that several developmental processes remain active in fruit bodies post-harvest. Proteins with antioxidant activities were identified, indicating the contribution of proteins to the antioxidant properties of L. edodes extracts. Antibacterial assays also reveal the activity of a serine protease inhibitor that strongly accumulates in the post-harvest fruit body grown on oak logs. Overall, this study contributes to the understanding of the impact of the log cultivation method on the production of Shiitake mushrooms richest in high-value bioactive compounds.